End-user perspectives to inform policy and program decisions: a qualitative and quantitative content analysis of lifestyle treatment recommendations by adolescents with obesity - M. Kebbe; A. Perez; A. Buchholz; T.-L. F. McHugh; S. D. Scott; C. Richard; M. P. Dyson; G. D. C. Ball (BMC, 2019)
Abstract Background Lifestyle modifications represent the first line of treatment in obesity management; however, many adolescents with obesity do not meet lifestyle recommendations. Given that adolescents are rarely consulted during health policy development and in the design of lifestyle interventions, their first-hand experiences, preferences, and priorities may not be represented. Accordingly, our purpose was to explore adolescents' lifestyle treatment recommendations to inform policy and program decisions. Methods Conducted from July 2017 to January 2018, this study adhered to a qualitative, crosslanguage, patient-oriented design. We recruited 19 13-17-year-old adolescents (body mass index [BMI] ≥85th percentile) seeking multidisciplinary treatment for obesity in geographically and culturally diverse regions of Canada. Adolescents participated in one-on-one, in-person, semi-structured interviews in English or French. Interviews were audio-recorded, transcribed verbatim, managed using NVivo 11, and analyzed using quantitative and qualitative content analysis by two independent researchers. Results Adolescents' recommendations were organized into five categories, each of which denotes health as a collective responsibility: (i) establish parental support within limits, (ii) improve accessibility and availability of 'healthy foods', (iii) limit deceptive practices in food marketing, (iv) improve accessibility and availability of varied physical activity opportunities, and (v) delay school start times. Respect for individual autonomy and decision-making capacity were identified as particularly important, however these were confronted with adolescents' partial knowledge on nutrition and food literacy. Conclusions Adolescents' recommendations highlighted multi-level, multi-component factors that influenced their ability to lead healthy lifestyles. Uptake of these recommendations by policy-makers and program developers may be of added value for lifestyle treatment targeting adolescents with obesity.